2017
DOI: 10.1002/jcb.25873
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs: The New Insight on Hypertrophic Scar

Abstract: Hypertrophic scarring (HS), a fibroproliferative disorder caused by abnormal wound healing after skin injury, is characterized by excessive deposition of extracellular matrix and invasive growth of fibroblasts. Numerous studies have reported that non-coding RNAs (ncRNAs) including microRNAs (miRNAs, miRs) and long non-coding RNAs (lncRNAs) play important roles in HS formation. Exploring non-coding RNA-based methods to treat scar would be instrumental for devising new effective therapies against scar. J. Cell. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 48 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Increasing evidence suggests that lncRNAs are involved in the progression of many diseases, including organ fibrosis (26)(27)(28) found that Smad3 induced expression of lncRNA Erbb4-IR, which mediates TGF-b1-induced renal fibrosis. A recent study from our group (31) found that lncRNA AK081284 was involved in the profibrotic effects of IL-17 during cardiac fibrosis in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that lncRNAs are involved in the progression of many diseases, including organ fibrosis (26)(27)(28) found that Smad3 induced expression of lncRNA Erbb4-IR, which mediates TGF-b1-induced renal fibrosis. A recent study from our group (31) found that lncRNA AK081284 was involved in the profibrotic effects of IL-17 during cardiac fibrosis in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, imbalanced apoptosis and proliferation in HSFs can cause hypertrophic scar formation. The proliferation or apoptosis of hypertrophic scar fibroblasts has been reported to be affected by the non-coding RNAs miR-200b, miR-21 and miR-143-3p [29]. We found that AC067945.2 overexpression slightly promoted early apoptosis in normal skin fibroblasts.…”
Section: Discussionmentioning
confidence: 58%
“…Numerous studies have reported that ncRNAs, including miRNAs and lncRNAs, participate in a variety of basic cellular processes, including ectopic regulation of gene expression, cell proliferation and differentiation, metabolism and apoptosis. With the development of microarray techniques, it has been demonstrated that ncRNAs have a key role in HS ( 21 ).…”
Section: Discussionmentioning
confidence: 99%